A case report of complete cricotracheal separation: an experience from the east coast of Malaysia - Atikah Rozhan; Adam Mohamad; Khairul Azhar M. Rajet; Mohd Zaki Ahmad; Suhaimi Bin Yusof; Wan Emelda Wan Mohamed; Bathma Devi Susibalan; Nik Mohd Syukra Nik Abd Ghani; Zamzil Amin Bin Asha’ari (Journal of Trauma and Injury)
Complete cricotracheal separation, which is the most severe type of laryngeal trauma, is an uncommonly seen injury that clinicians have limited experience in managing. However, it is potentially fatal. Due to limited exposure to this condition, mismanagement can occur, which may further aggravate the patient’s condition. The most crucial part of managing this injury is to establish a secure airway. Tracheostomy under local anesthesia is the preferred method of airway stabilization, in order to avoid further injuries to the airway caused by endotracheal intubation. Here, we discuss the management of complete cricotracheal separation based on a case experienced in the east coast region of Malaysia, where this type of injury is rarely encountered.